Análise do desempenho de um sistema de eletrocoagulação-flotação para o tratamento de esgoto doméstico visando reuso - Brächer, Gustavo Holz (2018)
The risks inherent to the inadequate domestic wastewater disposal, allied to the water growing demand and scarcity problems and the pollution of water sources, have highlighted the importance of adoption of treatment techniques that not only target the sewage final disposal, but also its reuse. In this context, electrocoagulation-flotation (ECF) has demonstrated the potential to confer good quality to wastewater, presenting positive aspects in an operational, economic and sustainable perspective. Thus, the objective of this study was to evaluate the performance of an ECF system in the domestic wastewater treatment and the possibility of the treated wastewater reuse. For this, it was carried out tests to determine the best conditions of domestic wastewater treatment in an ECF system, monitoring of the system performance and evaluation of the possibility of treated wastewater reuse. The domestic wastewater samples were obtained from an experimental effluent treatment plant, at the Federal University of Santa Maria. The ECF system was composed of a cylindrical acrylic reactor with a work volume of 1 L, which was equipped with two aluminum electrodes (9.10 x 7.50 x 0.05 cm) connected to a DC power supply. The determination of the best treatment conditions was performed by an effects study and a rotatable central composite experimental design, considering the operational parameters: electric current, distance between the electrodes, agitation and electrolysis time. However, during the tests, it was verified the need to adjust the initial pH of the samples, which became to be considered in the best conditions determination. The performance of the ECF system was monitored from the treatment of different domestic wastewater samples, under the best conditions established, based on the treated wastewater quality, the sewage constituents removal efficiency, the inputs demand, the waste production and the operational costs of the treatment. The evaluation of the possibilities of treated wastewater reuse was performed by comparison of its quality with the recommended by reuse guidelines, Brazilian standards and manual. Based on the results obtained, the best conditions for domestic wastewater treatment by ECF were: agitation of 262.5 rpm, distance between electrodes of 1 cm, electrolysis time of 25 min, electric current of 1.65 A and initial pH equal to 6. During the monitoring, the ECF system showed high removal efficiency of apparent color (97.9%), COD (82.9%), turbidity (95.8%), TS (66.9%) and phosphorus orthophosphate (> 98.2%), among the constituents analyzed, but the presence of residual aluminum was detected in an order of 10.5 mg∙L-1. The system also showed an average sludge production of 1537.9 g∙m-3 and an average operational cost of R$ 16.22 m-3, which can be substantially reduced with the practice of decentralized treatment and reuse. The treated wastewater presented propitious quality for the reuse in residential and urban environment. Thus, it was possible to conclude that the ECF system presented a good performance for the domestic wastewater treatment, demonstrating itself as an important alternative for the decentralized treatment and reuse of domestic wastewater.